Conformational flexibility of a free and TCR-bound pMHC-I protein investigated by long-term molecular dynamics simulations - Lisa Tomasiak; Rudolf Karch; Wolfgang Schreiner (BMC Immunology, 2022)
Abstract Background Major histocompatibility complexes (MHCs) play a crucial role in the cell-mediated adaptive immune response as they present antigenic peptides (p) which are recognized by host T cells through a complex formation of the T cell receptor (TCR) with pMHC. In the present study, we report on changes in conformational flexibility within a pMHC molecule upon TCR binding by looking at molecular dynamics (MD) simulations of the free and the TCR-bound pMHC-I protein of the LC13-HLA-B*44:05-pEEYLQAFTY complex. Results We performed long-term MD simulations with a total simulation time of 8 µs, employing 10 independent 400 ns replicas for the free and the TCR-bound pMHC system. Upon TCR ligation, we observed a reduced dynamic flexibility in the central residues of the peptide and the MHC α1-helix, altered occurrences of hydrogen bonds between the peptide and the MHC, a reduced conformational entropy of the peptide-binding groove, as well as a decreased solvent accessible surface area. Conclusions In summary, our results from 8 µs MD simulations indicate a restricted conformational space of the MHC peptide-binding groove upon TCR ligation and suggest a minimum simulation time of approximately 100 ns for biomolecules of comparable complexity to draw meaningful conclusions. Given the relatively long total simulation time, our results contribute to a more detailed view on conformational flexibility properties of the investigated free and TCR-bound pMHC-I system.